How Much Should We Expect? Family Caregiving of AIDS Patients in Rural Uganda - Kipp, Walter; Tindyebwa, Denis; Karamagi, Edna; Rubaale, Tom (Journal of Transcultural Nursing, 2007)
The aim of this study was to measure the burden of care for family caregivers of AIDS patients. A cross-sectional exploratory design was used to describe the care experiences of family caregivers of AIDS care recipients. A questionnaire was used to interview 120 family caregivers of AIDS patients from four rural areas in western Uganda. The questions asked were related to 12 domains of family caregiving. Care burden scores of caregivers were calculated. It was found that care burden scores were high in all domains except those regarding relationships within the families and substance abuse. Serious work overload and low health status were reported. The high burden of caregiving puts family caregivers at risk for decreased health status and increased social isolation and depression.
Keywords: Uganda; HIV/AIDS; Family caregiver; Care burden